The Unmasked Electorate: Co-Partisanship, Personal Experience, and Perceptions of COVID-19 Risk in Mexico - Bell-Martin, Rebecca V.; Díaz Domínguez , Alejandro (Revista Latinoamericana de Opinión Pública, 2021)
Research suggests partisanship influences individual perceptions of COVID-19 risk and preventative behaviors. We ask a distinct but equally urgent question: what factors are associated with variation in risk perception among co-partisans? Even among members of the same party, some individuals’ risk perceptions reflect the party line while others deviate from it. We explore this question in Mexico, where the president utilized his rhetoric to downplay the severity of the pandemic. Why do some of the presidents’ co-partisans perceive COVID-19 as a serious risk (despite partisan appeals to the contrary), while others do not? Drawing on theories of risk perception, we hypothesize that this variation is associated with personal risk experience, like knowing someone who contracted COVID-19. We test this hypothesis via a large-n survey of MORENA supporters. We find that personal experiences are consistently associated with variation in risk perception. Strength of partisan ties, meanwhile, is only activated when paired with risk experience.